2021
DOI: 10.1136/jmedgenet-2021-107776
|View full text |Cite
|
Sign up to set email alerts
|

Genetic testing in motor neuron disease and frontotemporal dementia: a 5-year multicentre evaluation

Abstract: IntroductionMotor neuron disease (MND) and frontotemporal dementia (FTD) comprise a neurodegenerative disease spectrum. Genetic testing and counselling is complex in MND/FTD owing to incomplete penetrance, variable phenotype and variants of uncertain significance. Affected patients and unaffected relatives are commonly referred to clinical genetics to consider genetic testing. However, no consensus exists regarding how such genetic testing should best be undertaken and on which patients.ObjectiveWe sought to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It is easy to underestimate the sense of disappointment this lack of molecular certainty entails, and individuals must be counselled about this before testing. Within the much larger apparently sporadic case population (~90%), a pathological variant will be identified in at least 10% of cases, with some studies proposing more than a fifth with clinically actionable findings 41 42. Even using the conservative estimate, 10% of the apparently sporadic cases of ALS is a greater number than 70% of the cases who report a family history.…”
Section: Introductionmentioning
confidence: 99%
“…It is easy to underestimate the sense of disappointment this lack of molecular certainty entails, and individuals must be counselled about this before testing. Within the much larger apparently sporadic case population (~90%), a pathological variant will be identified in at least 10% of cases, with some studies proposing more than a fifth with clinically actionable findings 41 42. Even using the conservative estimate, 10% of the apparently sporadic cases of ALS is a greater number than 70% of the cases who report a family history.…”
Section: Introductionmentioning
confidence: 99%
“…1 It is predicted that increasing numbers of people with MND will access genetic testing, a consequence of widening eligibility criteria and genetically targeted clinical trials (with one genetically targeted therapy suggesting clinical benefit). [2][3][4] This means more family members will become aware of their increased risk of developing the condition. The genetics of MND are complex, 5 but it is suggested that in up to 20% of people with MND, a pathogenic variant can be identified.…”
Section: Introductionmentioning
confidence: 99%
“…The typical survival from symptom onset is 2–5 years 1 . It is predicted that increasing numbers of people with MND will access genetic testing, a consequence of widening eligibility criteria and genetically targeted clinical trials (with one genetically targeted therapy suggesting clinical benefit) 2–4 . This means more family members will become aware of their increased risk of developing the condition.…”
Section: Introductionmentioning
confidence: 99%